Fractional View Analysis of Third Order Kortewege-De Vries Equations, Using a New Analytical Technique - Shah, Rasool; Farooq, Umar; Khan, Hassan; Baleanu, Dumitru; Kumam, Poom; Arif, Muhammad (Frontiers in Physics, 2020)
In the present article, fractional view of third order Kortewege-De Vries equations is presented by a sophisticated analytical technique called Mohand decomposition method. The Caputo fractional-derivative operator is used to express fractional derivatives, containing in the targeted problems. Some numerical examples are presented to show the effectiveness of the method for both fractional and integer order problems. The solution graphs have revealed that if the sequence of fractional-orders is approaches to integer order, then the fractional-order solutions of the problems are converge to an integer order solution. Moreover, the proposed method is straight forward and easy to implement and therefore can be used for other non-linear fractional-order partial differential equations.